PENGARUH KESEHATAN DAN KESELAMATAN KERJA TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI PT. BUMI PRATAMA KHATULISTIWA DESA MEGA TIMUR - B31111020, Henra Buana Sinaga (Jurnal Manajemen Update, 2016)
The purpose of this study was to determine the response and reaction of respondents to the research variables test and analyze the influence of occupational health and safety on the performance of the production employees of PT. Bumi Pratama Khatulistiwa Desa Mega Timur. The study design used in this study is causal design and population in this study is the production employees of PT. Bumi Pratama Khatulistiwa many as 41 respondents with sampling using saturation sampling as many as 41 respondents. This research uses descriptive analysis with quantitative approach using a questionnaire as a data collection and data analysis technique used is multiple regression analysis to measure the impact of independent variables on the dependent variable is the occupational health (X1) and safety (X2) as the independent variable and employee performance (Y) as the dependent variable. Based on the results of this study concluded that the implementation of occupational health and safety program and performance of employees in the production department of PT.Bumi Pratama Khatulistiwa Desa Mega Timur in good condition. There are significant occupational health and safety at work on employee performance. Keywords: Occupational Health, Safety and Employee Performance